Determinants of oral-health-related quality of life among adult people in Iran - Amir Hossein Nekouei; Shahla Kakoei; Hamid Najafipour; Sina Kakooei; Moghaddameh Mirzaee (Wolters Kluwer Medknow Publications, 2022)
Background: Oral health-related quality of life (OHRQoL) assesses the subjective perception of oral health and its impact on the quality of life. The aim of this study is to measure the OHRQoL and its determinants among adult people living in Kerman, Iran. Materials and Methods: In this cross-sectional study, a total of 5657 adult people (18-64 years) residing in the Kerman district, both in the rural and urban areas, were enrolled in the study between September 2014 and April 2018. The Oral Health Impact Profile (OHIP-14) and the oral health indices, such as the total decayed, missing, filled teeth (DMFT), community periodontal index (CPI), gingival index (GI), and xerostomia, were measured by an experienced dentist. The demographic variables of gender, age, educational status, and marital status were also recorded. The impact of the studied variables on OHRQoL was evaluated with multiple logistic regression. Results: Participants were 2239 (39.58%) men, and average age was 45.39. The mean scores for OHRQoL, DMFT, CPI and GI were respectively: 24.07 (7.76), 10.7 (6.86), 0.76 (0.96), 0.63 (0.8). The frequency of people with xerostomia was 37.4. 301 (53.3%) of people had poor quality of life related to oral health. In multivariable analysis, there was a statistically significant increase in OHRQoL with an increase in the DMFT (P < 0.001), xerostomia (P < 0.001), CPI, (P < 0.001). Men had a significantly higher OHIP score than women (P < 0.001). Conclusion: According to the results of this study, DMFT, xerostomia, and CPI scores are strongly related to OHIP scores. In addition, between CPI and GI scores, the CPI score is the better predictor.